Controlled Blood Pressure Factors in Hypertension Patients atArifin Achmad Hospital, Riau Province: Cross Sectional Study - Nugraha, Dimas Pramita; Bebasari, Eka (UI Scholars Hub, 2021)
Introduction. Hypertension is a chronic disease that causes 1 in every 7 deaths. Controlled blood pressure will reduce the complication of hypertension. The aim of this study was to determine the factors that influence controlled blood pressure. Methods.This research was conduct by using an observational method with a cross-sectional study design to analyze factors for controlled blood pressure. The population of this research was all of the hypertension patients at the internal medicine polyclinic in Arifin Achmad Hospital Riau Province. The sample was selected using accidental sampling method. Patient adherence level factor was measured using the Morisky medication adherence scale-8 (MMAS-8) questionnaire. The stress level factor was measured using the DASS-42 questionnaire. The family support factor was assessed using a family support questionnaire that refers to Friedman and House, while the level of knowledge was measured with the Guttman adoption questionnaire. Data analysis was performed by using chi-square and logistic regression tests. Results. From the analysis, it showed that only 16.7% of 96 respondents had controlled blood pressure. In patients with controlled blood pressure, the most common antihypertensive group factor used was calcium channel blocker (18.6%, RP=0.73, p=0.51), antihypertensive monotherapy factor (21.7%, RP=2.17, p=0.15), high knowledge level factor (21.3%, RP=2.11, p=0.16), good adherence factor (22.1%, RP=6.18, p=0.14), normal stress factor (16.2%, RP=3.78, p=1.00), and high family support (23.2%, RP=10.8, p=0.053). Conclusion. In this study, there were no factors that could be predictors of controlled blood pressure at Arifin Achmad Hospital Riau Province.